Evaluation of Multicomponent Changes of Schisandra chinensis Fruits with Different Drying Process by UPLC-QQQ-MS-Based Targeted Metabolomics Analysis - Yan-hua Sheng; Rui Wang; Yi-kai Wang; Meng-meng Li; Fang-xin Liu; Xin Huang; Chang-bao Chen (Journal of Chemistry)
Schisandra chinensis fruit is a famous tonic traditional Chinese medicine and healthy food. The chemical components of dried fruits may vary with the initial processing methods of fresh fruits. Therefore, in this study, the influence of drying was evaluated based on targeted metabolomics analysis. The ultrahigh performance liquid chromatography-triple quadrupole mass spectrometry (UPLC-QQQ-MS) was applied in determination of multicomponent including lignans, organic acids, and oligosaccharides. The fresh fruits of Schisandra chinensis were processed by natural drying in the sun, hot air drying and vacuum drying at different temperatures, and vacuum freeze drying, respectively. The contents of lignans, organic acids, and oligosaccharides in different fruit samples were quantified and statistically analyzed by partial least squares discriminant analysis (PLS-DA). The variation of totally 10 lignans, 5 organic acids, and 9 oligosaccharides with different drying process were compared. The results showed that the drying time of natural drying method was much longer than the other methods using instrument. For hot air and vacuum drying samples, most of lignans, organic acids, and oligosaccharides gradually decreased with the increase of temperature. And the appearance of fruit drying at higher temperature was dark red. At the same processing temperature, vacuum drying takes longer time than hot air drying. In addition, organic acid and oligosaccharide contents of vacuum freeze drying treated samples were higher than the other processed samples significantly. According to the targeted metabolomics analysis, the lignans, organic acids, and oligosaccharides markers were screened out for holistic quality evaluation of Schisandra chinensis fruits. In comprehensive consideration of multicomponent, drying time, fruit appearance and storage, and production feasibility, hot air drying at 50°C is more suitable for the process of Schisandra chinensis. The result is expected to provide a scientific basis for the selection of proper method for drying process of fresh Schisandra chinensis fruit.